Analysis and Design of Information Systems for Control of Raw Materials in UD. YRS Alumunium Work Using EOQ Method - Assaji Assaji; Rudy Arijanto (Tech-E, 2020)
In the current era of globalization, information technology and information systems are developing very fast. YRS Alumunium Work is a furniture company that manufactures cupboards, stove racks, sinks, and especially for storage of household items. The problems currently being faced by businesses, among others; (a) recording still using stationery and books or still using manual recording methods, (b) ineffective stock checking, (c) sudden out of stock, to solve the problem it is proposed to make a system using the web that can be integrated into stock by a calculation method. With UML scenario depiction (activity diagrams, usecase diagrams, class diagrams, sequence diagrams). To check the inventory of goods easily done effectively, know the minimum amount of stock, and must place an order again using the EOQ (Economic Order Quantity) method. By using the eoq method, it takes into account that for bolts to get an economical amount of inventory as much as 522.01 with a safety stock of 21 will place an order again when the stock becomes 50 and the total inventory cost is 110 458.4418.